COMBINATION OF ELECTROACUPUNCTURE THERAPY WITH HERBAL ROSEMARY (ROSEMARINUS OFFICINALIS L.) IN CASE OF OBESITY - Widya Retnaning Puspita; Abdul Rahman; Suhariningsih; Suryani Dyah Astuti; Nurul Fitriyah; Winarno; Katherine; Ahmad Faizin Alma; Mohammad Zulkarnaen (Jurnal Biosains Pascasarjana, 2023)
Obesity or overweight is a condition that occurs when the quantity of body fat tissue compared to total body weight is greater than the normal state. Diet, exercise, psychological factors, heredity, hormones, and drug side effects are a few of the factors that might cause obesity. Gastric heat syndrome was present in the patient in this case study. The patients received electrostimulator-assisted acupuncture treatment 12 times for a total of 15 minutes at the following points: Fenglong (ST40), Neiting (ST44), Sanyinjiao (SP6), and Quchi (LI11), and was also given the herbal remedy rosemary (Rosmarinus officinalis L.) for 28 days, taken twice daily. Through the activation of PPAR- g, inhibition of prankeas lipase, and inhibition of pre-adipocyte development into adipocytes, carnosic acid, a component of rosemary, helps people lose weight. Additionally, carnosic acid stimulates the excretion of fat in feces. According to the case study results, the patient's body weight dropped from 77.6 kg to 73.9 kg. This indicates that acupuncture treatments at the points Fenglong (ST40), Neiting (ST44), Sanyinjiao (SP6), and Quchi (LI11) together with the administration of rosemary herbs can result in weight loss of up to 3.7 kg over the course of 28 days.